Asuhan Keperawatan Jiwa Pada Ny. W Dengan Perilaku Kekerasan Diruang Srikandi Rumah Sakit Jiwa Daerah Surakarta - Wardani, Agetia; , Arif Widodo, A.Kep., M.Kes (2015)
Background:Mental health is a situation where a person who is free from mental disorders, and have a positive attitude to describe the maturity and personality. In 2012 the number of people with mental disorders worrying globally, approximately 450 milion people surfer from mental disorders- third live in developing countries, and as many as 8 out of 10 people with mental disorders do not receive treatment. Based on these problems the authors are interested to provide nursing care to patients with mental disorders especially in client with violent behavior in order to prevent the risk of injuring one selft, others, the environment and the emergence of other psychiatric disorders and to improve the welfare in achieving the desired objectives. Purpose: To know the soul of nursing care in the clients with violent behavior. Results:Afternursing care approach implementation strategy of the client with violent behavior, the results obtained the clients able to express anger without hurting, blaming others and control violent behavior by means of physical (take a deep breathand at the pillow), take medication regularly and talk with good. Conclusion: In this case found two diagnoses that risk injuring yourself, other and the environment associated with violent behavior and the risk of violent behavior associated with low self estheem. Adequate hospital facilities and the optimal role of nurses is indispensable in providing nursing care so that clients can to apply the way have been taught by nurses. Key words: Violent behavior, Nursing care, Mental disorders.